Respuesta :
Possibly you refer to the integral,
[tex]\displaystyle\int\frac{\sin2x}{24+\cos^2x}\,\mathrm dx[/tex]
Recall the double angle identity,
[tex]\cos^2x=\dfrac{1+\cos2x}2[/tex]
Then the integral is equivalent to
[tex]\displaystyle\int\frac{\sin2x}{24+\frac{1+\cos2x}2}\,\mathrm dx=2\int\frac{\sin2x}{49+\cos2x}\,\mathrm dx[/tex]
Let [tex]y=49+\cos2x[/tex] so that [tex]\mathrm dy=-2\sin2x\,\mathrm dx[/tex]. Then the integral becomes
[tex]\displaystyle-\int\frac{\mathrm dy}y=-\ln|y|+C[/tex]
[tex]\implies\displaystyle\int\frac{\sin2x}{24+\cos^2x}\,\mathrm dx=-\ln|49+\cos2x|+C[/tex]
We can rewrite this to try to get it in a form that more resembles the original integrand.
[tex]-\ln|49+\cos2x|+C=-\ln\left|2\left(24+\dfrac{1+\cos2x}2\right)\right|+C[/tex]
[tex]=-\ln2-\ln\left|24+\cos^2x\right|+C[/tex]
[tex]=-\ln\left|24+\cos^2x\right|+C[/tex]
where the constant term [tex]-\ln2[/tex] got absorbed into the general constant [tex]C[/tex].
Using substitution, the result of the integral is given by:
[tex]-\ln{(49 + \cos{2x})} + C[/tex]
We want to calculate the following integral:
[tex]\int \frac{\sin{2x}}{24 + \cos^{2}x} dx[/tex]
The following identity is used to simplify the cosine squared:
[tex]\cos^2{x} = \frac{1 + \cos{2x}}{2}[/tex]
Replacing into the integral:
[tex]\int \frac{\sin{2x}}{24 + \frac{1 + \cos{2x}}{2}} dx[/tex]
[tex]\int \frac{2\sin{2x}}{48 + 1 + \cos{2x}} dx[/tex]
[tex]\int \frac{2\sin{2x}}{49 + \cos{2x}} dx[/tex]
The substitution is:
[tex]u = 49 + \cos{2x}[/tex]
[tex]du = -2\sin{2x}dx[/tex]
[tex]dx = -\frac{1}{2\sin{2x}} du[/tex]
Hence:
[tex]\int \frac{2\sin{2x}}{49 + \cos{2x}} dx[/tex]
[tex]\int \frac{2\sin{2x}}{u} -\frac{1}{2\sin{2x}} du[/tex]
[tex]\int -\frac{1}{u} du[/tex]
[tex]-\ln{u} + C[/tex]
Since [tex]u = 49 + \cos{2x}[/tex], the result as a function of x is:
[tex]-\ln{(49 + \cos{2x})} + C[/tex]
A similar problem is given at https://brainly.com/question/22077165